The Cooperative Health Level Based on Ministerial Degree No. 6, Year 2016 - Iif Masripatul Laela; Liana Rahardja (STIE-JIC, 2021)
The purpose of this research is to assess the health level of Jasa Marga Bakti (JMB) Cooperative based on the Ministry of Small and Medium Enterprises Decree Number: 06/Per/Dep.6/IV/2016. This is qualitative research with data collected through library research, interviews, and documentation. The results show that the cooperative is “Quite Healthy” from 2015 to 2017 with a score of 66.00 in 2015, 67.00 in 2016 and 2017, but “Under Supervision” in 2018 and 2019 with a score of 65.25. Furthermore, components such as increased income to cover current liabilities, rise in own capital, and appropriate measurement of risk reserves need to be considered irrespective of whether the majority are good. This research indicates that the JMB cooperative acts as a loan intermediary for the members with the bank and earns profits from setting administrative costs. The results are expected to be helpful for the commander and members of the cooperative in improving the financial and overall performance of the cooperative.